2015
DOI: 10.1002/mnfr.201400674
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and chemopreventive targets of sulforaphane in humans following consumption of broccoli sprouts or a myrosinase-treated broccoli sprout extract

Abstract: Scope Sulforaphane (SFN), an isothiocyanate derived from crucifers, has numerous health benefits. SFN bioavailability from dietary sources is a critical determinant of its efficacy in humans. A key factor in SFN absorption is the release of SFN from its glucosinolate precursor, glucoraphanin, by myrosinase. Dietary supplements are used in clinical trials to deliver consistent SFN doses, but myrosinase is often inactivated in available supplements. We evaluated SFN absorption from a myrosinase-treated broccoli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
123
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 32 publications
7
123
0
Order By: Relevance
“…However, there were marked increases in serum SFN levels following ingestion of whole BS, although it is possible that the concentrations of SFN were not sufficiently high to have biologic activity. The total SFN conjugate levels detected in our study were similar to some of the published studies, although a lot of variability exists in the SFN conjugate/metabolite measured as well as timing and methods of detection, making it difficult to compare systemic SFN levels among studies 10, 11, 27 . Second, our study was conducted in adults with atopic asthma and the other studies were all conducted in healthy subjects, so it is possible that the dose and/or duration of treatment needed among a population of asthmatics, who may have impaired activation of Nrf2 and induction of the antioxidant pathway, may be greater than that needed for healthy adults.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, there were marked increases in serum SFN levels following ingestion of whole BS, although it is possible that the concentrations of SFN were not sufficiently high to have biologic activity. The total SFN conjugate levels detected in our study were similar to some of the published studies, although a lot of variability exists in the SFN conjugate/metabolite measured as well as timing and methods of detection, making it difficult to compare systemic SFN levels among studies 10, 11, 27 . Second, our study was conducted in adults with atopic asthma and the other studies were all conducted in healthy subjects, so it is possible that the dose and/or duration of treatment needed among a population of asthmatics, who may have impaired activation of Nrf2 and induction of the antioxidant pathway, may be greater than that needed for healthy adults.…”
Section: Discussionsupporting
confidence: 80%
“…Two doses, 12h apart compared to consuming a single dose, resulted in higher plasma concentrations of SFN metabolites 24 h post-consumption. However, neither 200 μmol once daily or 100 μmol twice daily induced significant antioxidant gene expression in blood 27 , suggesting that more frequent dosing of whole BS would not result in biologic activity. This study, like ours, suggests that whole BS, despite resulting in marked increases in serum SFN, has little biologic activity in doses that could reasonably be consumed by an adult.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additional studies are needed to evaluate dose-responses and responses of other relevant molecular targets to consuming foods and supplements that provide SFN. While the supplements used in this study were well-tolerated, recent work indicated that other broccoli extract preparations may be more bioavailable and should be considered for use in future studies to enhance SFN absorption from these forms (33). Overall, this work provides important information for future larger population-based clinical trials investigating the impacts of consuming dietary sources of SFN.…”
Section: Discussionmentioning
confidence: 93%
“…Creatinine concentrations were determined using the Jaffe reaction method as previous described (33). SFN and SFN metabolite concentrations in urine were normalized using creatinine concentrations to control for differences in urine volume.…”
Section: Methodsmentioning
confidence: 99%